The Implementation of General Principles of Convention on The Rights of The Child During Covid-19 Pandemic in The City of Serang - Ridwan, Ridwan; Jaya, Belardo Prasetya Mega; Imani, Sarah Haderizqi (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2022)
Convention on The Rights of The Child is the most comprehensive international legal instrument of human rights to promote and protect rights of children. In the late 2019, Coronavirus Disease 19 outbreak started. This pandemic then has led to socio-economic impact as a result of preventive and controlling actions. This pandemic has also affected the fulfillment of child’s rights including the rights of children in The City of Serang. This research was aimed at investigating the implementation of general principle of Convention on The Rights of The Child during Covid-19 pandemic in the city of Serang. This study applied normative research method, which is a research discussing legal aspects by studying literature sources on the applied regulations. The result of the study shows that the implementation of general principle of Convention on The Rights of The Child, consisting of the principle of non-discrimination, the best interest of the child, the right to life, survival and development, and the right to be heard, went well along with the establishment of Child Social Welfare Institute to serve children with special needs (LKSA), Integrated Service Centre for the Empowerment of Women and Children (P2TP2A) to receive complaints on the violation of children’s rights, Serang’s Children Forum as a media where children of Serang can participate. The implementation of the right to survival was not as good because Working group (Pokja) for adverse effect following immunization (KIPI) special for children has not effectively implemented.